Spatial Analysis of the Effects of Women’s Socioeconomic Status on Divorce Rates in Turkey - Ayça Özekin; Burcu Süküti (Sosyal Siyaset Konferansları Dergisi)
The purpose of this study is to investigate how much and in what direction divorce rates in Turkey are affected by women’s socioeconomic status. In the literature, it is stated that the most important reasons for the increasing divorce rates are the changing female roles in society and the family structure, the individualization brought about by industrialization, the increase in welfare levels, and the facilitation of divorce opportunities. The change in the place and role of women in the family structure is associated with the increase in women’s participation in the labor force and their increase in the level of education, which occurred alongside industrialization. At this point, the regional differentiation of socioeconomic status indicators for women reveals the need for a spatial study of the effects of these variables on the divorce rate. In the study, the relationship between the socioeconomic status indicators of women in Turkey and the divorce rates were examined by estimating the Spatial Autocorrelation (SAR) and Spatial Error (SEM) Models for 26 sub-regions in the Turkish Statistical Regional Units Classification (NUTS) Level 2. The findings revealed that socioeconomic status indicators of women have regionally different effects on divorce rates in Turkey, in line withthe expectations. While the divorce rates increased throughout the country over the years examined, it was observed that they were lower in the Eastern regions of the country than in the Western regions. In addition, it has been observed that the Independence Hypothesis is valid at high education levels, while low education level has a decreasing effect on divorce rates.